Public relations and tourism: finding public relations’ role in communicating tourist destination - Santoso, Nobertus Ribut; Negoro, Sherly Hindra (Jurnal Studi Komunikasi, 2019)
Public relations plays essential roles in communicating and building image of tourist destinations in order to attract a significant number of tourists. Starting from this consideration, this research investigates the role of hotel public relations practitioners in communicating Yogyakarta as the tourist destination. The growth of tourists arriving in Yogyakarta cannot be separated from the role of hotel public relations practitioners in communicating Yogyakarta as the great place to visit. This research employed descriptive qualitative approach. The data was gathered by conducting interviews with three hotel public relations practitioners in Yogyakarta who have experienced in this field at least one year. Based on activities they did to communicate Yogyakarta as the tourist destination, it can be categorised that hotel public relations practitioners in Yogyakarta play communication technician role by using the beautiful and unique cultures and landmarks as backgrounds to communicate their hotels to tourists, using both conventional and new media to strengthen the image of Yogyakarta.